Classification studies of a novel variety “Jewellery in the yellow sea” of Subgen Camellia - LI Fang; FU Cheng-xin; XIA Yi-ping; XU Bi-yu (浙江大学学报. 农业与生命科学版)
A study of clssification was carried out with Camellia olerfera, “Flowering cherry” Camellia sasanqua, “Small rose” Camellia hiemalis, “Autumn peony” Camellia japonica, “Mosaic peony” Camellia japonica and unclassified “Jewellery in the yellow sea” as materials. The taxonomic location of “Jewellery in the yellow sea” was comprehensively evaluated on the results from comparison of morphological features, pollen grains observation under scanning electron microscope and isozyme analysis of esterase (EST) and peroxidase (POX). It was suggested that “Jewellery in the yellow sea” is a novel variety of Camellia sasanqua.